Teaching economics of climate change and sustainability as an introductory interdisciplinary elective using critical reading of supplementary sources. Issue 4 (4th August 2021) - Basu, Suchandra
Abstract: Critical thinking skills are widely considered to be important transferable skills gained from taking college-level economics courses that are also highly valued by employers. Yet, the literature on intentionally teaching critical thinking skills in undergraduate economics classes is still relatively sparse. The author of this article outlines an innovative approach to teaching critical thinking skills through class participation activities designed to promote critical reading of outside sources in an interdisciplinary climate economics course. The course goal is to equip students with the skills to articulate how economists contribute to the thinking on climate change and apply basic economics tools to explain and evaluate climate policy.